Lithium‐Sulfur Batteries: Functionalized Boron Nitride Nanosheets/Graphene Interlayer for Fast and Long‐Life Lithium–Sulfur Batteries (Adv. Energy Mater. 13/2017). Issue 13 (July 2017) - Fan, Ye; Yang, Zhi; Hua, Wuxing; Liu, Dan; Tao, Tao; Rahman, Md Mokhlesur; Lei, Weiwei; Huang, Shaoming; Chen, Ying
Abstract : In article number1602380, Weiwei Lei, Ying Chen, and co‐workers design a thin and selective interlayer structure of functionalized boron nitride nanosheets/graphene to decrease the charge transfer resistance and mitigate the shuttling problem of lithium sulfur batteries. The new and advanced interlayer can effectively entrap the polysulfide (PS) and exhibit ultrahigh cycling abilities as compared to batteries without the interlayer.